The Prevalence of Depressive and Insomnia Symptoms, and Their Association With Quality of Life Among Older Adults in Rural Areas in China - Yang, Juan-Juan; Cai, Hong; Xia, Lei; Nie, Weicheng; Zhang, Yulong; Wang, Song; Shi, Yudong; Ng, Chee H.; Liu, Huanzhong; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: There are few studies on the epidemiology of depression, insomnia, and their association with quality of life (QOL) in older adults living in rural China. This study examined the prevalence of depressive and insomnia symptoms, and their association with QOL in community-dwelling older adults in a rural area in Anhui province, China. Methods: This was a cross-sectional study conducted in the rural areas of four cities (Hefei, Huaibei, Anqing, and Xuancheng) in Anhui province between July and October, 2019 using random sampling method. All community-dwelling residents from the selected villages who met the study entry criteria were invited to participate in this study. Depressive and insomnia symptoms and QOL were assessed with the Chinese version of self-reported Center for Epidemiological Survey Depression Scale (CES-D), the Insomnia Severity Index (ISI) and the 26-item World Health Organization Quality of Life Brief version (WHOQOL-BREF), respectively. Results: A total of 871 older adults were included. The prevalence of overall depressive symptoms, insomnia symptoms, and comorbid depressive and insomnia symptoms were 34.0% [95% confidence intervals (95% CI): 30.8–37.1%], 45.7% (95% CI: 42.4–49.0%) and 20.3% (95% CI: 17.6–23.0%), respectively. Older adults with depressive symptoms, insomnia symptoms, and comorbid depressive and insomnia symptoms had lower scores in QOL compared to those without. Depressive symptoms were positively associated with living with families [Odd Ratio (OR) = 1.82, 95% CI: 1.31–2.54] and negatively associated with current drinking (OR = 0.49, 95% CI: 0.33–0.72). Insomnia symptoms were negatively associated with fair and good financial status (fair: OR = 0.53, 95% CI = 0.38–0.75; good: OR = 0.30, 95% CI = 0.14–0.64) and current drinking (OR = 0.64, 95% CI = 0.45–0.93), and positively associated with more frequent major medical conditions (OR = 1.32, 95% CI = 1.16–1.51). Comorbid depressive and insomnia symptoms were positively associated with living with families (OR = 2.02, 95% CI = 1.36–3.00), and negatively associated with fair and good financial status (fair: OR = 0.61, 95% CI = 0.41–0.89; good: OR = 0.34, 95% CI = 0.12–0.95) and current drinking (OR = 0.57, 95% CI = 0.35–0.92). Conclusion: Depressive and insomnia symptoms were common in older adults living in rural areas in China. Considering the negative health outcomes caused by depressive and insomnia symptoms, regular screening and effective treatments should be developed for this population.